Erdoğan and the Muslim Brotherhood: an outside-in approach to Turkish foreign policy in the Middle East. (20th October 2022) - Taş, Hakkı
ABSTRACT: Amidst multiple foreign policy flip-flops of the Turkish government, the Middle East is where observers agree most about the explanatory priority of ideational factors over realpolitik calculations. The assertive foreign policy activism to extend the country's role in the region has largely been linked to the Islamist leanings of the ruling Justice and Development Party (AKP). This study revisits Turkey's Middle East policy with a particular focus on the AKP's relations with the Muslim Brotherhood (Ikhwan al Muslimin), which marked Turkish foreign policy formulation and implementation in multiple theatres from Yemen to Egypt to Libya. Using a neoclassical realist approach, it argues that the AKP's ideological ties to the Ikhwan are significant for the availability of new resources but Turkish foreign policy behavior in the Middle East, including relations with the Ikhwan, reflects a grand strategy to respond to systemic and sub-systemic stimuli.